1958
DOI: 10.1021/jf60086a002
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Residues, Residues in Milk from Dairy Cattle Treated with Methoxychlor for Fly Control

Abstract: Phytopathology Soc. 20, 21 (abstract) (1952).(83) Ríes, S. K., "Studies on the Selective Mechanism of Chloro-IPC (Isopropyl '-3-Chlorophenylcarbamate),"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1960
1960
2012
2012

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…after spraying with the same concentration of a wettable-powder suspension. Helrich et al (7), working with herds of 4 to 6 animals, reported residues of a few tenths of a part per million of methoxychlor in milk shortly after spraying. On the other hand Birk and Dixon (7) and Cheng et al {3) published data showing that less than 0.1 p.p.m.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…after spraying with the same concentration of a wettable-powder suspension. Helrich et al (7), working with herds of 4 to 6 animals, reported residues of a few tenths of a part per million of methoxychlor in milk shortly after spraying. On the other hand Birk and Dixon (7) and Cheng et al {3) published data showing that less than 0.1 p.p.m.…”
mentioning
confidence: 99%
“…Helrich et al (7), working with herds of 4 to 6 animals, reported residues of a few tenths of a part per million of methoxychlor in milk shortly after spraying. On the other hand Birk and Dixon (7) and Cheng et al {3) published data showing that less than 0.1 p.p.m. of methoxychlor is excreted in milk following topical applications.…”
mentioning
confidence: 99%